Jewish sovereignty and the inclusive exclusion of Palestinians: Shifting the conceptual understanding of politics in Israel/Palestine - Jamal, Amal (Frontiers in Political Science, 2022)
This article explores the dynamics of Jewish sovereignty when dealing with the massive presence of millions of Palestinian presence in its sphere of power. It does so by looking at foundational Israeli documents. Two of the best to serve our goal are the Israeli Declaration of Independence (IDI), adopted in 1948 and the Basic Law – Israel: The Nation State of the Jewish People (Nation-State law), enacted in 2018. The aim is not to compare and contrast the two documents as much as to deduce the deep meaning of Jewish sovereignty embedded in them, and its ramifications on the Palestinian presence in the land this sovereignty dominates. It is argued that the two foundational documents establish an underlying differentiation between dissimilar realms of existence. Whereas they construct Jewish presence as dynamically sovereign, they render Palestinians as threatening strangers who should be subordinated or silenced in order to be tolerated. This means that the documents explicate the main characteristics of Jewish sovereignty. They also implicitly relate to treatment of the Palestinians, whether considering the periods before or after 1967. In order to achieve its goal, the article utilizes Jacques Derrida’s concept of diffirance, demonstrating that the Israeli strategy is best understood as the discursive and practical effort to establish differences between different groups of Palestinians and exploit the gaps between these differences in order to sustain its control over the millions of them who live in the realm of Jewish sovereignty. It shows that differance is about enforcing gaps between forms of being in the world. These forms are best articulated through the differentiation introduced by Martin Heidegger between the ‘worldless’, ‘the poor in world’ and the ‘world forming’.